2008
DOI: 10.1002/jssc.200700377
|View full text |Cite
|
Sign up to set email alerts
|

Headspace single‐drop microextraction of herbal essential oils

Abstract: A method employing the headspace single-drop microextraction (HS-SDME) is presented for the determination of essential oils in dried herbal leaves. By optimising the key experimental parameters, a linear response for the individual target compounds was obtained in the concentration range from LOQ to 4 mg/mL (r(2) = 0.9912-0.9998), with LODs from 3.3 up to 20.5 microg per 100 g of dried leaves, and the repeatability within the RSD of 2.1-8.9%. The HS-SDME-based procedure, enabling a rapid and simple analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Thus, it is crucial to perform the respective optimisation in order to obtain the good recovery. Because this optimisation has already been performed and published [24], in this work only final extraction conditions are presented. So it was found that 2 μL of p-xylene at 70°C for 90 s using 0.5 g of sample in a 10 mL sampling vial are suitable conditions for the HS-SDME method.…”
Section: Single-drop Microextraction Methods Applicationmentioning
confidence: 99%
“…Thus, it is crucial to perform the respective optimisation in order to obtain the good recovery. Because this optimisation has already been performed and published [24], in this work only final extraction conditions are presented. So it was found that 2 μL of p-xylene at 70°C for 90 s using 0.5 g of sample in a 10 mL sampling vial are suitable conditions for the HS-SDME method.…”
Section: Single-drop Microextraction Methods Applicationmentioning
confidence: 99%
“…Tea infusions are commonly prepared by simulating the conditions under which these infusions are prepared in everyday practice by steeping a packet of teas in boiling water for a prescribed period of time (5–15 min) 13,14 . Analyses based on the LPME technique have been reported using various parts of plant samples, including root, 15–18 stem, 16 leaf, 16,19,20 fruit, 16,21 leaves, 22–29 flowers 30–33 and seeds 34–36 …”
Section: Samplesmentioning
confidence: 99%
“…Conventional procedures for the extraction of a plant constituents usually require a relatively large amount of sample. In contrast, microextraction procedures typically work with lesser amounts of plant material, which can range from several tens of milligrams (10 mg, 14–16,37–39 20 mg, 40 40 mg, 31 50 mg 21,26,34,41,42 ) to one or several hundred milligrams (100 mg, 17,24,29,43–50 150 mg, 51 200 mg, 35,52 0.3 g, 32,53 0.4 g, 54 0.5 g, 25,28,55–60 0.6 g, 61 0.7 g, 62 0.750 g, 18 0.9 g 63 ). However, in some cases weights ranging from one 19,22,30,64–66 or more grams (2 g, 14,20,23,36,67–72 2.5 g 73 to 5 g 74 ) have also been used.…”
Section: Samplesmentioning
confidence: 99%
“…One can find, however, various modifications of SDME that more or less differ from the above‐described general procedure. Examples of the application the two most commonly used modes of SDME—HS and DI—can be found in the Supporting Information …”
Section: General Procedures Of Single‐drop Microextraction (Sdme)mentioning
confidence: 99%